Real-time dynamic analysis of J-laying. (August 2016) - Zan, Yingfei; Yuan, Lihao; Han, Duanfeng; Bai, Xu; Wu, Zhaohui
Abstract: This paper presents a real-time numerical model for the dynamic analysis of an offshore pipeline in a J-laying simulation. The feasibility of the model is demonstrated by comparison with results obtained using a catenary model; specifically, there is good agreement for the pipeline configuration and tension force. Furthermore, as dynamic factors, nonuniform current, layered current flow and vessel motion are considered. The results show that the dynamic forces are important factors acting on the pipeline. An investigation of the computational efficiency shows that the calculation speed is more than 480 Hz when the pipeline is divided into 60 nodes. This demonstrates that the present model is compact and computationally effective and thus suitable for real-time applications.